PENGARUH BIAYA PRODUKSI DAN PERPUTARAN PERSEDIAAN TERHADAP LABA BERSIH PADA PERUSAHAAN MANUFAKTUR INDUSTRI SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) Periode 2014-2019 - Dewi Haryanti; Herry Winarto (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2021)
The purpose of this study was to determine the effect of production costs and inventory turnover on Net Profit in industrial manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange in 20142019.This study uses a purposive sampling technique in the sampling method and the sampling that meets the criteria are 9 manufacturing companies. The data used in this research is secondary data.The results of this study indicate that the two independent variables, namely production costs and inventory turnover partially affect net income, and simultaneously production costs and inventory turnover affect net income with a significance level of 0.000 < 0.05 with an Adjusted R2 value of 0.651 which shows that 65.1% of net income is influenced by production costs, inventory turnover and the remaining 34.9 is influenced by other variables outside of the variables in this study.